Measuring the Deadweight Loss from Taxation in a Small Open Economy. A general method with an application to Sweden - Peter Birch Sørensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2011)
The paper develops a simple general equilibrium framework for calculating the marginal deadweight loss from taxation in a small open economy. The framework allows a decomposition of the deadweight loss from each tax instrument into the losses stemming from the contraction of the different tax bases. The paper describes a method of calibrating the model which exploits the links between the various factor supply elasticities implied by the standard life cycle model. It also develops a method of estimating effective tax rates that is consistent with optimising household and firm behaviour. To illustrate how the model works, it is calibrated to a data set for Sweden. The quantitative results highlight the importance of accounting for the interaction between the major tax bases when estimating deadweight loss.
Keywords: H21; 330; Deadweight loss; tax policy in a small open economy; Steuerbelastung; Besteuerungsverfahren; Allgemeines Gleichgewicht; Kleine offene Volkswirtschaft; Schweden